Analisis Wacana Strategi Dakwah Sultan Agung Adi Prabu Hanyokrokusumo - Jalal udin; Zainil Ghulam; Abdul Ghofur (Institut Agama Islam Syarifuddin Lumajang, 2021)
The study of Sultan Agung's da'wah strategy is a study to reveal historical facts that occurred in the past to be used as a guide in achieving a better future. Given that the glory of Mataram was in the power of Sultan Agung who led Mataram from 1613 to 1645. The theoretical framework used in this study is discourse analysis which is used as a knife to analyze Sultan Agung's da'wah strategies. Discourse analysis which is used as a theoretical framework uses the concept of Van Dick (1968). While the da'wah strategy referred to is the method of da'wah in general, namely the da'wah bil hal, the dakwah bil lisan, and the dakwah bil qalam This research resulted in the first findings that Sultan Agung's da'wah strategy was carried out with three oral da'wah strategies, carried out by Sultan Agung as seen in Sultan Agung's negotiations in expanding the power of Islamic Mataram at that time with neighboring kingdoms or countries. Da'wah bil Qalam, was done with phenomenal works, namely literary gending and astronomical works of the Kejawen calendar. Da'wah bilhal, that the personality of Sultan Agung is a personality that is gentle but firm in making decisions as the king has given uswah to his people. The second conclusion is that in social cognition, a king must have strength both physically, psychologically and mystically. In the social context, Sultan Agung's leadership is always colored by cultures that have always been developed by Sultan Agung, which is then carried out an acculturation of indigenous culture with Islamic culture. Keywords:Discourse Analysis, Da'wah Strategy, Sultan Agung Adi Prabu Hanyokrokusumo.